Kritik Terhadap Perubahan RUU KUHP: Perspektif Hukum Pidana dan Hak Warga Negara - Alex Prayoga Sidabutar; Tifany Laura Balqis; Lammarito Lumban Gaol; Isnaniah Isnaniah; Taslima Ameliya Taufik; Ramsul Nababan; Maulana Ibrahim (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The proposed changes to the Draft Law on the Criminal Code (RUU KUHP) have attracted widespread attention from various parties. This research aims to examine and criticize these changes, especially from the perspective of criminal law and citizens' rights. This study uses qualitative research with a library approach in obtaining data for research results. The research results show that there are many problems related to changes to the Criminal Code Bill, which include the addition and deletion of several articles. The ambiguity of legal concepts, the possibility of abuse of power, and the consequences for individual freedom are the main focus of criticism. Changes may also affect citizens' rights and the judicial process.